Studi Literature: Pendidikan Anak Usia Dini pada Masa Reformasi di Indonesia - Wilanda, Novia Sri; Rahmadini, Rahmadini; Hadiyanto, Hadiyanto (Pedagogi: Jurnal Ilmu Pendidikan, 2024)
This article presents an analysis of the development of Early Childhood Education (ECED) procedures in reform-era Indonesia. The main focus is on policy implementation and the important role of families and communities in supporting it. The research was conducted using a desk study method to analyze relevant literature. The results show progress in ECD policy development but also identify challenges such as inequitable access and quality of ECD in different regions. Reform-era education reforms emphasize decentralization and competency-based systems, but implementation has been uneven. The role of family and community is considered crucial in supporting the success of ECD by involving them in formal, non-formal and informal education processes. This involvement is important to create an environment that supports the holistic development of young children. The study recommends a systemic approach to education reform, integrating changes to learning experiences, learning systems, local management and legislation systems.